Female mice with HSD17B1 inactivation show mild hyperandrogenism without notable impact on reproductive function or bone - Junnila, Arttu; Petruk, Nataliia; Heikelä, Hanna; Postila, Pekka; Hakkarainen, Janne; Martinez-Nieto, Guillermo; Uceda-Rodriguez, Esperanza; Ruiz-Pino, Francisco; Tena-Sempere, Manuel; Ohlsson, Claes; Sipilä, Petra; Heino, Terhi J.; et al. (Oxford University Press, 2026)
17β-hydroxysteroid dehydrogenase 1 (HSD17B1) is the primary enzyme responsible for the activation of estrone (E1) to estradiol (E2) in ovaries and extra-gonadal tissues of both humans and rodents. In the present study, molecular modelling indentified the substitution of His222 in the human HSD17B1 enzyme with glycine in the mouse as the key determinant for the different steroid specificity between the species. Furthermore, Ser143Ala mutation at the active site of mouse HSD17B1 resulted in a total loss of E1 to E2 conversion by HSD17B1. This resulted in elevated intraovarian and circulating E1 concentrations in adult HSD17B1 Ser143Ala knock-in (KI) females, but no changes in E2 concentrations were observed compared to the wild-type mice. Androstenedione and dihydrotestosterone were also elevated in the HSD17B1-KI ovaries, associated with elevated circulating luteinizing hormone (LH). However, the effect of HSD17B1 inactivation on female reproductive development and function was mild, primarily resulting in a slight decrease in ovarian weight in older HSD17B1-KI mice, without notable effects on fertility. Expression of genes related to steroid biosynthesis, mitochondrial metabolism, and known markers of PCOS was found to be upregulated in adult HSD17B1-KI ovaries. However, no alterations in the structure or function of extra-gonadal tissues were observed, and the uterus and bone phenotypes in the HSD17B1-KI females were unaffected. Our results demonstrate that the blockade of HSD17B1-dependent E2 synthesis is successfully compensated for in mouse in vivo, resulting in only a mild ovarian estrogen and androgen imbalance, but no significant adverse effects on reproductive or bone health.